Given an equation in the form of
`y = mx + b`
the slope is given by m, and the y-intercept is given by b.
We'll transform the given equation into that form:
`y = 3(x - 4) + 1`
Multiply each term in the parentheses by 3:
`\implies y = 3x - 12 + 1`
Next, combine like terms by adding 1 to -12:
`\implies y = 3x - 11`
Therefore the slope of the given equation is 3 and the y-intercept is -11.
Recall that the point-slope formula is:
y - y1 = m(x - x1) where m is the slope and (x1, y1) is a point.
Its simple step of algebra to change what you have into that form. Subtract 1.
y - 1 = 3(x - 4)
Its now readily apparent that you have a slope of 3 and one point on it is (4, 1)